Disaster risk in a New Keynesian model - Maren Brede (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
This paper develops a simple New Keynesian model incorporating a small time-varying probability that the economy is struck by a disaster in the future. The model's main prediction is that a small increase in the disaster probability causes a recession in the economy, speci cally due to limited saving opportunities inasmuch as the model abstracts from capital accumulation. By contrasting its ndings to the ones of a comparable real business cycle model, this paper evaluates how the disaster hypothesis has been used and modelled in the existing literature.
Keywords: E21; E31; E32; 330; time-varying risk; disasters; rare events; nominal rigidities